"An eye that saw more lofty things than mortal eye is now struck blind" (Hölderlin): German politics and aesthetics in Jean-Marie Straub and Danièle Huillet's Der Tod des Empedokles (1986) and Jean-Luc Godard's Allemagne année 90 neuf zéro (1991). Issue 1 (31st December 2022) - Pletinck, Karel
ABSTRACT: The sudden flourishing of reflections on light, nature and poetry that occurred from the mid-80s onwards in the cinema of Jean-Luc Godard, Danièle Huillet and Jean-Marie Straub, could not fail to surprise. Between their reputation as Brechtian, materialist filmmakers and these seemingly apolitical reflections, developed in conjunction with their appeal to Hölderlin's "idealist" poetry, there seems to be an insurmountable rift. By situating their aesthetics in the broader framework known as "aesthetic modernity", i.e. art and philosophy of art since the end of the 18 th century (cf. J.M. Schaeffer, J. Rancière), I demonstrate how films such as Der Tod des Empedokles (1986) and Allemagne année 90 neuf zéro (1991), not so much exhibit a shift to conservatism with this "sudden" interest in nature and poetry, but, rather, the manifestation of a Romantic contradiction characteristic of modern aesthetics. In a period of disillusionment, these "Brechtian" filmmakers increasingly turned to a German literary and philosophical tradition that praised the "revelationist" potential of poetry, while they, simultaneously and still with revolutionary fervour, reflected on Germany's troubled political past and present. I will argue that we can understand this alignment of revolution and revelationism from the perspective of their indebtedness to an antimodern worldview that perceives of the modern age as being in decline, to which these filmmakers oppose a utopian striving towards a "new world", captured in a Romantic discourse of light and vision.